Effect of Root Extract Fractions of Kyllinga triceps Rottb on Streptozotocin Induced Diabetic Rats (Stamford Journal of Pharmaceutical Sciences, 2011)
The present study was aimed to evaluate the root extract fractions of Kyllinga triceps (KT) for their antidiabetic potential on streptozotocin induced diabetes in neonatal rats. Diabetes was induced by a single intraperitoneal injection of Streptozotocin (90mg/kg) to 48±2h old neonatal rats. Effect of root extract fractions (toluene, ethyl acetate, 1- butanol at 50 &100 mg/kg.) were tested for their antihyperglycemic activity by measuring their fasting blood glucose level in diabetic rats at 0,2,4,6,8,12 & 24 h after the treatment. In sub acute study ethyl acetate fraction of KT (EAKT) was administered daily to diabetic rats orally at a dose of 100mg/kg for 28 days. Body weight of the animals and blood glucose level were observed at weekly interval during the study. Cholesterol, triglycerides, insulin, SGPT, ALP, creatinine and total proteins level in serum were also estimated at the initial and after 28 days of the treatment. As the preliminary investigation conducted in our lab on methanolic extract of the roots of KT had showed significant oral glucose tolerance with 200 mg/kg in normal rats. Oral administration of fractions of the plant significantly reduced the fasting blood glucose level in diabetic rats. Among the fractions, EAKT was found to be more effective. Further, in sub-acute study, EAKT, showed a significant anti diabetic activity by reversal of the altered afore said serum biochemical parameters. The results of the study are substantiating the traditional claim of the roots of Kyllinga triceps in the treatment of diabetes with a scope for development of antidiabetic herbal drug from EAKT.   Key words: Antidiabetic activity; Kyllinga triceps; Ethyl acetate fraction; Streptozotocin. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8863 SJPS 2011; 4(1): 25-30